2021
DOI: 10.1038/s41598-021-81360-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and resolution of hypertension in obese African American bariatric cohort

Abstract: Weight reduction continues to be first-line therapy in the treatment of hypertension (HTN). However, the long-term effect of bariatric malabsorptive surgical techniques such as Roux-en-Y Gastric Bypass (RYGB) surgery in the management of hypertension (HTN) is less clear. African Americans (AA) are disproportionately affected by obesity and hypertension and have inconsistent outcomes after bariatric surgery (BS). Despite a plethora of bariatric literature, data about characteristics of a predominantly AA bariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
3
0
1
Order By: Relevance
“…In this sense, Chaudhary et al have shown a strong association of hypertension with all adiposity parameters in T2DM patients [ 39 ]. Gandotra et al have reported that in African American adults with obesity, the prevalence of T2DM in hypertensive patients is eight times as high as that in nonhypertensive individuals [ 45 ]. In line with these results, our current study revealed that HTEW participants are more influential in glucose abnormalities than HTNW and NHEW patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Chaudhary et al have shown a strong association of hypertension with all adiposity parameters in T2DM patients [ 39 ]. Gandotra et al have reported that in African American adults with obesity, the prevalence of T2DM in hypertensive patients is eight times as high as that in nonhypertensive individuals [ 45 ]. In line with these results, our current study revealed that HTEW participants are more influential in glucose abnormalities than HTNW and NHEW patients.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the amelioration of comorbid diseases, the resolution of type II diabetes mellitus depended on HbA1c < 6% or fasting blood glucose less than 100 mg/dl in the absence of hypoglycemic drugs [18]. The complete resolution of hypertension was based on blood pressure less than 120/80 without using medications, while its improvement was considered a reduction in dosage or number of anti-hypertensive drugs or systolic and diastolic pressure with the similar drugs [19]. Normal lipid profile after stopping the medications was demarcated as resolved dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Bariatric surgery (BS), a sustainable approach to achieving substantial weight loss, not only is beneficial to the cardiovascular system through the modification of cardiometabolic risk factors (e.g., diabetes) and the reduction in major adverse cardiovascular events but also can improve renal functions, alleviate obesity-related inflammation, and enhance patient survival in those with severe obesity [13] , [14] , [15] , [16] , [17] . In addition, patients with obesity who underwent BS were found to have a significantly lower risk of respiratory tract infections compared to those who did not receive the procedure [18] .…”
Section: Introductionmentioning
confidence: 99%